An Experimental Study on the Influence of Injection Timing Variations on Diesel Engine Performance Using Dexlite and Cooking Oil Blends - Rahayu Mekar Bisono (International Journal of Science, Engineering, and Information Technology, 2025)
This study aims to analyze the effect of firing point variations on the performance of the S195 type diesel engine using a mixture of Dexlite fuel and cooking oil. The firing point variations used were 17°, 18°, and 19° before TDC, with the fuel mixture containing 30% cooking oil. Tests were conducted to measure thermal efficiency, specific fuel consumption (SFC), and engine output power. The results showed that proper firing point settings can increase thermal efficiency and decrease SFC, especially at an angle of 18°, where the highest thermal efficiency was 24.80% and the lowest SFC was 0.342 kg/kWh. In addition, the use of this mixed fuel was able to provide more perfect combustion than pure Dexlite fuel. The conclusion of this study suggests the need for good engine maintenance and proper injection timing to improve the performance of diesel engines based on mixed fuel, as well as an effort to utilize cooking oil as a renewable energy source.